Income Misperception and Populism - Thilo N. H. Albers; Felix Kersting; Fabian Kosse (Center for Economic Studies and ifo Institute (CESifo), 2022)
We propose that false beliefs about the own current economic status are an important factor for explaining populist attitudes. Along with the subjects' receptiveness to right-wing populism, we elicit their perceived relative income positions in a representative survey of German households. We find that people with pessimistic beliefs about their income position are more attuned to populist statements. Key to understanding the misperception-populism relationship are strong gender differences in the mechanism: Misperception triggers income dissatisfaction for both men and women, but the former are much more likely to channel their discontent into affection for populist ideas.
Keywords: D63; D72; D91; P16; 330; perception; income; populism